Henri Bergson et les conservateurs espagnols (1907-1940)/I - Camille Lacau Saint-Guily (Cahiers de Civilisation Espagnole Contemporaine)
The Great War hardens the relationship between France and Spanish conservatives, rather germanophile since the Revolution of 1789. The philosopher Henri Bergson, a very strong intellectual authority in his country between 1900 and 1920, enlisted as a missionary of the Allied cause in the world. This diplomatic engagement increases the effect of religious rejection, as a Catholic "modernist", since 1907, he must face a political backlash. In addition to being considered the enemy thinker of official Catholic philosophy, neo-Thomism, he is described by the Spanish press as the conservative three-headed monster created by the head of the French Action, Charles Maurras. Indeed, various conservatives papers such as ABC, El Debate, La Época or the catholic fundamentalist newspaper El Siglo Futuro depict him, in his three-head image, as an emblem of the Jacobin Revolution, Reform and decadent Romanticism. The writers of the Spanish radical right as José María or Salaverría or Eugenio D'Ors develop, during the War of 1914-1918 and later, an axiological and political anti-Bergsonism inspired among others by French nationalism. Bergsonism represents for them, by his «intuitionism», his anti-intellectualism, a decadent thinking, impressionist, semitic, antithetical to conservative noucentista thinking.